2020
DOI: 10.1186/s12885-020-07055-1
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic ablative body radiotherapy (SABR) combined with immunotherapy (L19-IL2) versus standard of care in stage IV NSCLC patients, ImmunoSABR: a multicentre, randomised controlled open-label phase II trial

Abstract: Background: About 50% of non-small cell lung cancer (NSCLC) patients have metastatic disease at initial diagnosis, which limits their treatment options and, consequently, the 5-year survival rate (15%). Immune checkpoint inhibitors (ICI), either alone or in combination with chemotherapy, have become standard of care (SOC) for most good performance status patients. However, most patients will not obtain long-term benefit and new treatment strategies are therefore needed. We previously demonstrated clinical safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 71 publications
(84 reference statements)
0
27
0
Order By: Relevance
“…These studies provide important information for the design of clinical trials, suggesting that IO should be combined concurrently with fRT or it should be administered shortly after ablative radiation doses, depending on the type of IO. The clinical translation of these results can be demonstrated by the recently started international multicentric randomized Phase 2 trial ImmunoSABR (NCT03705403), where L19–IL2 is combined with ablative radiation doses in a sequential manner [ 102 ].…”
Section: Window Of Opportunity To Achieve Synergy Between Radiothementioning
confidence: 99%
See 1 more Smart Citation
“…These studies provide important information for the design of clinical trials, suggesting that IO should be combined concurrently with fRT or it should be administered shortly after ablative radiation doses, depending on the type of IO. The clinical translation of these results can be demonstrated by the recently started international multicentric randomized Phase 2 trial ImmunoSABR (NCT03705403), where L19–IL2 is combined with ablative radiation doses in a sequential manner [ 102 ].…”
Section: Window Of Opportunity To Achieve Synergy Between Radiothementioning
confidence: 99%
“…We have demonstrated in several preclinical studies the ability of RT to synergize with L19–IL2 and to induce durable systemic antitumor responses [ 96 , 97 , 149 ]. Our promising results prompted us to conduct clinical trials investigating the toxicity, which is deemed safe or tolerable, and therapeutic efficacy of this combination [ 102 , 150 ] (NCT02735850, NCT03705403, NCT04604470).…”
Section: Immunotherapeutic Options and Conventional Radiotherapymentioning
confidence: 99%
“…A clinical phase II study recently demonstrated that hu14.18-IL2 given in combination with GM-CSF and the differentiation inducing agent isotretinoin is safe and tolerable, and showed anti-tumor activity in patients with relapsed/ refractory neuroblastoma (135). Several other IL2-antibody fusions have advanced to clinical trials, including huKS-IL2 (136), NHS-IL2 (128) and L19-IL2 (137). The combination of RT (5 x 4 Gy) followed by NHS-IL2 after first-line chemotherapy in metastatic non-small cell lung cancer (NSCLC) patients was well tolerated (128).…”
Section: Future Perspective: Multifunctional Antibody Development and In Situ Tumor Ablationmentioning
confidence: 99%
“…This concept is related to the wider definition of “oligometastatic” disease (“oligo” = “few”) that refers to a limited number of metastases and/or metastatic sites characterized by a more indolent behavior than a polymetastatic disease [ 5 , 6 ]. Although there is no consensus on the appropriate cut off to define the oligometastatic state, generally up to 3–5 lesions in 1–3 organs are defined in international guidelines and are commonly accepted [ 7 , 8 , 9 ].…”
Section: Definition and Biology Of Oligoprogression In Ansclcmentioning
confidence: 99%